Comparison of the thermal, dynamic mechanical and morphological properties of PLA-Lignin & PLA-Tannin particulate green composites. (1st December 2015) - Anwer, Muhammad A.S.; Naguib, Hani E.; Celzard, Alain; Fierro, Vanessa
Abstract: The study of Lignin and Tannin as filler materials in PLA-based polymeric systems has been uncommon in literature. Composites of PLA-Lignin with 5, 10, 15 wt% Lignin and PLA-Tannin with 5, 10, 15 wt% Tannin were fabricated using injection moulding. SEM morphology reveals Lignin forms droplet like dispersions within the PLA matrix in contrast to Tannin. The particle size of Lignin within the matrix is also 10–150 times smaller than Tannin. Isothermal frequency sweeps on the composites show that storage modulus of PLA-Tannin composites starts to degrade at 15 wt% filler concentration and damping rises. PLA-Lignin composites do not show such degradation in storage modulus. The tensile strength of both PLA-Lignin and PLA-Tannin composites falls with increase in filler content. Lignin has a more inhibitory effect on PLA crystallization than Tannin. The onset of thermal degradation of PLA-Lignin and PLA-Tannin composites occurs at slightly lower temperatures than pure PLA.